The Effect of the Online and Offline Blended Teaching Mode on English as a Foreign Language Learners’ Listening Performance in a Chinese Context - Yuhong Jiang (Frontiers Media S.A., 2021)
With the rapid development of digitalisation, multimedia and network-based communication technology, all walks of life are undergoing change and development driven by the application of the internet to conventional industries. Especially because of the outbreak of coronavirus disease of 2019 (COVID-19), English teaching and learning modes are undergoing revolutionary changes worldwide (Wong et al., 2020). Online courses and materials have become the norm for students, and combined with offline English learning activities, an online and offline blended learning mode has ultimately emerged (Graham, 2006; Whittaker, 2013). Whereas blended learning has been considered in several contexts, it has been less investigated in the field of blended English learning mode for the listening comprehension ability and emotional experiences of young learners of Chinese English as a foreign language (EFL) while doing the tasks. Thus, this study focussed on the achievement and experience of Chinese EFL junior high school students during blended learning using Quizlet software as the online learning tool. This study aimed to explore the following: (1) the effect of the online and offline blended mode on the learning outcomes of students and (2) the experience of students while engaging with blended tasks in terms of their learning interest, attitude, and strategy use in English listening learning. A 4-month teaching intervention involving the online and offline blended mode was conducted in English listening classes. Adopting mixed-methods qualitative and quantitative research, this study examined the engagement process of two classes of students and analysed data from their English listening tests and follow-up in-depth interviews. The results suggested that the blended activity was conducive to enhancing the listening performance of students. Moreover, the attitudes of students toward English listening learning shifted from a relatively negative engagement to a more positive one. Meanwhile, the interest of students grew and their learning strategies became more diversified. These findings have implications for English teaching and learning activity design for young learners.